Impacts of mental fatigue and sport specific film sessions on basketball shooting tasks - Daub, B. D.; McLean, B. D.; Heishman, A. D.; Peak, K. M.; Coutts, A. J. (European Journal of Sport Science, 2022)
Purpose The aim of this investigation was to examine the impact of mental fatigue on basketball specific shooting performance, utilising the newly developed basketball Standardized Shooting Task (SST).